Volume 3: 30th Computers and Information in Engineering Conference, Parts a and B 2010
DOI: 10.1115/detc2010-28613
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Tactile Interactions With New Product Materials: An Analysis of Depth Impressions Based on Associative Concept Networks

Abstract: Depth impressions are an inward associative layer of the expressed impressions of humans. To analyze tactile interaction, it is essential to examine what users feel and imagine and how they create depth impressions by touching and looking at different materials. On the basis of tactile interactions, this study captures and analyzes users' depth impressions on materials. We propose impressionable new tactile material for design from the viewpoint of depth impressions and emotional engineering. We employed a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Materiality has been studied as material understanding and material strategy for design (Vallgårda, 2009). Previous studies have shown that user impressions of materials in tactile interactions depend on the level of user familiarity with the material (Nagai, Georgiev and Taura, 2010). For example, congruence in perceptions may also facilitate processing and contribute to positive evaluations (Van Rompay and Pruyn, 2011).…”
Section: Experience Of Objectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Materiality has been studied as material understanding and material strategy for design (Vallgårda, 2009). Previous studies have shown that user impressions of materials in tactile interactions depend on the level of user familiarity with the material (Nagai, Georgiev and Taura, 2010). For example, congruence in perceptions may also facilitate processing and contribute to positive evaluations (Van Rompay and Pruyn, 2011).…”
Section: Experience Of Objectsmentioning
confidence: 99%
“…People need to touch to know and understand the man-made objects they are manipulating, and ultimately attribute meaning to the objects. The first attempts to penetrate deeper into the topic of tactile experience of product materials show that user impressions depend on how "natural" the material is perceived to be, including how well users are accustomed to it (Nagai, Georgiev and Taura, 2010). Moreover, such impressions are related to material preferences.…”
Section: Tactual Experiencementioning
confidence: 99%
See 3 more Smart Citations